Three‐dimensional nonwoven flax fiber reinforced polylactic acid biocomposites. Issue 7 (13th November 2013) - Alimuzzaman, Shah; Gong, R. Hugh; Akonda, Mahmudul
<x xml:space="preserve">Abstract</x> Three‐dimensional (3D) shell‐structured PLA/Flax biocomposites were fabricated using a novel method incorporating the 3D nonwoven web‐forming process. PLA and flax fibers were blended in the fiber opening stage and converted to webs on the 3D mold using the air‐laying principle. The 3D webs were then consolidated by through‐air thermal bonding. The compression molding technique was used finally to convert the 3D webs to the biocomposites. The relationship between the main process parameters and the properties of the biocomposites was investigated. The results show that with increasing flax fiber content, the crush failure load, total energy absorption, specific energy absorption, and crush efficiency increased. The crushing properties decreased with increased molding temperature, but the crushing properties are not significantly affected by the molding time. The physical properties of 3D biocomposites were also evaluated and the appropriate processing parameters for 3D biocomposites were established. POLYM. COMPOS., 35:1244–1252, 2014. © 2013 Society of Plastics Engineers